PERTIMBANGAN HAKIM DALAM PENJATUHAN HUKUMAN KEPADA PELAKU TINDAK PIDANA PEMALSUAN SURAT (Studi Putusan Nomor 2573/Pid.B/2021/PN.Mdn) - Weni Sartika Putri Wahyuni Loi (Jurnal Panah Hukum, 2023)
Forgery is the act of changing/imitating by using deception so that it resembles the original. One of the crimes of forgery of letters that has been examined and tried by the Supreme Court is decision number 2573/Pid.B/2021/PN.Mdn. In that decision, the perpetrator was sentenced to 6 (six) months in prison for violating Article 263 paragraph 1 in conjunction with Article 56 paragraph 2 of the Criminal Code. The type of research used by the author is normative research using the statutory approach, case method, and analytical approach. Data collection was carried out using secondary data obtained through library materials consisting of primary legal materials and secondary materials. The data analysis used is descriptive qualitative analysis and the conclusion is drawn using the deductive method. Based on the findings of the research and discussion, it can be concluded that the judge's considerations in imposing sentences to the perpetrators of the crime of forgery consist of juridical and non-juridical judges' considerations, the judge sentenced him to 6 (six) months in prison for violating Article 263 paragraph (1) paragraph Jo Article 56 paragraph (2) of the Criminal Code. Based on the judge's juridical considerations, the factors revealed in court, the defendant's actions have been proven and convincingly committed the act of forging letters. Where the defendant is an employee of PT. Capella Medan by giving a sentence of 6 (six) months in prison. Meanwhile, in the non-juridical consideration of the judge, there are things that are aggravating the actions of the defendant to cause harm to PT. Capella Medan while in mitigating those attached to the defendant. The author suggests that judges in examining, adjudicating in deciding a criminal case are expected to be more careful in imposing punishments on the perpetrators of the crime of forgery of letters in order to provide or create justice, certainty, and benefit with the applicable rules, to provide a deterrent effect for not committing acts. law enforcement again